(untitled) (LIS TODAY, 2021)
Abstract: Moral philosophy is a branch of philosophy that can help us to examine and lead an ethical life. Ethics is a branch of philosophy that “involves systematizing, defending and recommending concepts of right and wrong behaviour”. Ethical subjects can be partitioned into four sections proposals are meta-ethics, descriptive ethics, normative ethics and applied ethics. Most of the ethical standards remain consistent with time and they do not change over the period. There have been a few prominent instances of plagiarism over the most recent couple of years. Institutions must take the responsibility for ensuring academic standards and for emphasising, to both students and faculty, the importance of maintaining the highest standards of integrity in academic research”. COPE(The Committee on Publication Ethics) is focused on teaching and supporting editors, publishers and those associated with publication ethics with the point of moving the way of culture of publication towards one where moral practices turns into an ordinary aspect of the publishing society. WAME is a philanthropic deliberate relationship of editors of companion checked on medical journals from nations all through the world who look to encourage worldwide participation among and training of medical journal editors. Literary theft recognition instruments for e-learning Professionals recognize a job well done.